Development of Graphic Organizer Based LKPD in Reading Texts in Grade IV Elementary School - Ulfa Gustianti (Yayasan Thaifah Manshurah Pekanbaru, 2023)
The purpose of this study was to determine the development of the feasibility of graphic organizer-based LKPD in grade IV reading text. This study uses the development research method. The 4D model consists of 4 stages, namely: define, design, development and dissemination. The instruments that will be used in this study are validation questionnaires, teacher response questionnaires and student response questionnaires. The data analysis technique used is quantitative method, which is a method of quantitative data analysis techniques through scientific calculations. The results of this study the experts stated that the LKPD product as an alternative material for learning Indonesian Language in grade IV Elementary School developed by the researcher was very feasible. The overall average validation score by both material expert validators and media experts amounted to 89.58, the results of the teacher response questionnaire obtained an average assessment score of 90.00 and the results of the overall student response questionnaire obtained an average assessment score of 93.75.